Social interaction in games. (1st January 2011) - Stenros, Jaakko; Paavilainen, Janne; Mäyrä, Frans
Due to the popularity of social media networks and the games played on those platforms interest in the so-called social games has piqued. This article looks at those games in the context of general social aspects of game play. By approaching game play as an activity, it is possible to distinguish between different kinds of social interaction: the sociability players engage in around the game and the social play contained and mediated by the game. In charting the social space of playing, this article shows the inherent social aspects of singleplayer games – and the solitary aspects of social games.